2005
DOI: 10.1097/01.ju.0000152119.28959.3a
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthesia During 10 Core Biopsy of the Prostate: Comparison of 2 Methods

Abstract: Intraprostatic administration of local anesthesia significantly decreases the pain associated with prostate biopsy compared with periprostatic nerve block. It is a simple, safe and rapid technique that should be considered in all patients undergoing transrectal ultrasound guided prostate biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 17 publications
4
32
0
1
Order By: Relevance
“…69 The reported complication rate associated with periprostatic nerve block ranges from 2-4%. 17,20,69,70 No significant complication differences were found with intraprostatic analgesia injection 64,67,68 or topical agents. 22,63,71 Of note, reported morbidity is confounded by the fact that many of the complications (i.e.…”
Section: Complicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…69 The reported complication rate associated with periprostatic nerve block ranges from 2-4%. 17,20,69,70 No significant complication differences were found with intraprostatic analgesia injection 64,67,68 or topical agents. 22,63,71 Of note, reported morbidity is confounded by the fact that many of the complications (i.e.…”
Section: Complicationsmentioning
confidence: 96%
“…64 Intra-prostatic injection provides local anesthetic to sensory fibers within the parenchyma of the prostate, which have a high sensitivity to pain. Secondly, peri-prostatic nerve block does not anesthetize the anterior part of the gland, while intra-prostatic injection does.…”
Section: Intra-prostatic Injection Of Local Anestheticmentioning
confidence: 99%
“…15 Although Mutaguchi and colleagues asserted that intraprostatic infiltration was superior to periprostatic infiltration, 16 we routinely perform both periprostatic and intraprostatic infiltration as the latter is not associated with additional pain and adds little to the overall duration of the procedure. As long as one steers clear of the urethra, hematuria is uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is congruent with prior studies that have also suggested that the apical biopsy is associated with significant pain. 7,14,[17][18][19] The discomfort of apical biopsies is related to the anatomic relation between the prostatic apex and innervation of the rectum below the dentate line. We have used the ''rectal sensation test,'' 18 but have not found it helpful when patients are in the prone jackknife position.…”
Section: Discussionmentioning
confidence: 99%